Antidiabetic components from a mangrove actinobacterial culture in Vietnam - Hoang, Kim Chi; Tran, Thi Hong Ha; Le, Huu Cuong; Tran, Thi Nhu Hang (Vietnam Journal of Marine Science and Technology, 2025)
In our quest for mangrove microbial candidates with antidiabetic potential in Vietnam, actinobacterial strains were isolated and screened for inhibitory activity against carbohydrates digesting enzymes α-amylase and α-glucosidase. As a result, Streptomyces sp. strain S-X10.2 emerged as a microbe of interest since its ethyl acetate extract exhibited inhibition rates of 62.66 ± 2.50 and 58.95 ± 1.27% against α-glucosidase and α-amylase, respectively, at test concentration of 500 µg/mL. Using column chromatography integrated with bioassays, XA1 was separated from the ethyl acetate extract and appeared as the most abundant as well as the most bioactive among purified products of the chemical isolation. XA1 showed α-amylase and α-glucosidase inhibitory activities with IC50 values of 294.62 and 335.22 µg/mL, respectively. Further GC/MS identification revealed the presence of saturated and unsaturated fatty acids in XA1, with oleic acid (27.70 %), palmitic acid (23.70 %), and linoleic acid (21.80 %) as the most major compounds. These results revealed evidence of bioactive fatty acids in ethyl acetate extract of an actinobacterial strain’s fermented culture. Furthermore, they contributed to drawing a new aspect in exploiting natural products from mangrove microorganism.